Low-temperature metastable-to-equilibrium phase transitions in Fe–Ga alloys. (June 2022) - Mohamed, A.K.; Palacheva, V.V.; Cheverikin, V.V.; Vershinina, T.N.; Balagurov, A.M.; Muralikrishna, G.M.; Esakkiraja, N.; Divinski, S.V.; Wilde, G.; Golovin, I.S.
Abstract: Significant differences between the properties of Fe–Ga alloys (Galfenols) in their metastable and equilibrium states, as well as discrepancies between existing Fe–Ga phase diagrams and for the transition rates for the metastable to equilibrium state have been detected and discussed. In view of both the fundamental understanding and the technological importance of these alloys, the exact knowledge of the equilibrium phase diagram, metastable phases, and the transition rates between different phase states towards equilibrium are necessary and require further clarification. We have studied the influence of alloy composition, annealing temperature and annealing time (up to 1800 h) on the metastable-to-equilibrium phase transitions in binary Fe–Ga using a coherent set of complementing methods, including diffraction methods (X-ray and neutron diffraction), scanning electron microscopy, and electron backscatter diffraction. We propose several important changes to the low-temperature part of the binary Fe–Ga diagram close to the Fe-rich corner and a new method based on interdiffusion couples for varying the structure and phase states of Fe–Ga alloys. Highlights: A quasi-binary Fe–Ga phase diagram is built to correct existing phase diagrams. Most alloys do not achieve their equilibrium state even after annealing up to 1800 h. A diffusion couple approach results in a fast-track determination of the diagrams.